FKBN (State Defense Cadre Forum) Lampung's Obstacles in Increasing State Defense Awareness: A Sociological Study of Social Agents and Civil-Military Cooperation - Nurdin, Bartoven Vivit; Sindi, Arsella Mutiara; Tivantara, Branden Jaya (Jurnal Pertahanan dan Bela Negara, 2026)
This study aims to examine the sociological aspects of the State Defense Cadre Forum (FKBN), as a social agent in increasing awareness of State Defense and the obstacles faced. FKBN is a partner of the Ministry of Defense which was formed on the basis of national resource management, in this case Human Resources (HR). However, so far the role of FKBN in increasing awareness of state defense and management of national resources (SDN) in areas such as Lampung, is still stagnant, weak and tends to be unable to provide the expected results. Lampung is a heterogeneous area as a result of migration, so it is very important to instill awareness of State Defense. The Sociological aspects of Defense, namely Human, Culture, social structure and Defense have not been fully seen in the formation of FKBN. This study uses a qualitative method with data collection techniques through in-depth interviews, observation and documentation. Data analysis was carried out using data reduction, data display and data verification.The results of the study indicate that FKBN has not provided a significant impact on increasing awareness of national defense, there is no innovation, recruitment of cadres that does not pay attention to the quality of human resources. The main problem is the inability of the forum to be a symbol and agent for the social structure, in addition to the problem of lack of budget, activity permits and relatively elderly members because young people are not interested in joining this forum. The community is also still influenced by the binary opposition mindset (civilian vs. military), namely considering national defense as a military matter not a civilian matter, considering national defense as part of the military hegemony over civilians, still seeing threats to the state as a military matter.